Removal of Three Phenolic Compounds [Polychlorinated biphenyl (PCB 105, PCB 118 & PCB 150)] from Aqueous Solutions by Fiber Palm as a Biosorbent - Athraa Hameed Mekky (Journal of Global Pharma Technology, 2016)
The aim of this work is to determine the potential of application of palm fiber as a biosorbent for removing of three phenolic compounds[polychlorinated biphenyl (PCB)] (2,3,3',4,4'-Pentachlorobiphenyl PCB 105, 2,3',4,4',5- Pentachlorobiphenyl; PCB 118, and 2,2',3,4',6,6'-Hexachlorobiphenyl; PCB-150 from aqueous solutions. The effect of pH, adsorbent dosage and contact time were investigated. Increase in the pH to neutrality resulted in the increase in the phenolic compounds adsorption capacity. The results showed that the increase in the fiber palm dosage to 0.5g/0.1L significantly increased the phenolic compounds adsorption rates. The adsorption process was fast, and it reached equilibrium in 30 min. contact time. The Freundlich and Langmuir adsorption models were used for mathematical description of the adsorption equilibrium and it was found that experimental data fitted very well to both Freundlich and Langmuir models. These results indicate clearly the efficiency of fiber as a low-cost solution for these compounds in aqueous solutions treatment and give some preliminary elements for the comprehension of the interactions between palm fiber as a bioadsorbent and the very polluting compounds from aqueous solutions.Keywords: Freundlich, Langmuir, Palm fiber and phenolic compounds.